Modelled natural and excess radiocarbon: Sensitivities to the gas exchange formulation and ocean transport strength - Mueller, S. A.; Joos, F.; Plattner, G.-K.; Edwards, N. R.; Stocker, T. F. (Global Biogeochemical Cycles, 2008)
Observation-based surface ocean Δ 14 C distributions and regional inventories for excess, bomb-produced radiocarbon are compared with results of two ocean models of intermediate complexity. By applying current descriptions of the air-sea gas exchange the models produce similar column inventories for excess 14 C among all basins. This result is robust across a wide range of transport parameter settings, but inconsistent with databased inventories. In the absence of evidence of fundamentally different gas exchange mechanisms in the North Atlantic than in the other basins, we infer regional North Atlantic 14 C inventories which are considerably smaller than previous estimates. The results further suggest that the gas exchange velocity field should be reduced by (19 ± 16)%, which corresponds to a global mean air-sea gas transfer rate for CO 2 in seawater of 17.1 ± 3.3 cm/h -1 , to find good agreement of simulated quantities with a range of data-based metrics.